Supramolecular cage encapsulation as a versatile tool for the experimental quantification of aromatic stacking interactions. Issue 5 (27th November 2018) - Bravin, Carlo; Licini, Giulia; Hunter, Christopher A.; Zonta, Cristiano
Abstract : A Double Mutant Cycle is built up using a supramolecular cage that binds two aromatic carboxylates in a stacked geometry is used to quantify aromatic stacking interactions. Abstract : The widespread presence of aromatic stacking interactions in chemical and biological systems, combined with their relatively small energetic contribution, have led to a plethora of theoretical and experimental studies for their quantification and rationalization. Typically, π–π aromatic interactions are studied as a function of substituents to gather information about the interaction mechanism. While experiments suggest that aromatic interactions are dominated by local electrostatic contacts between π-electron density and CH groups, theoretical work has raised the possibility that direct electrostatic interactions between local dipoles of the substituents may play a role. We describe a supramolecular cage that binds two aromatic carboxylates in a stacked geometry such that the aromatic substituents are remote in space. Chemical Double Mutant Cycles (DMCs) were used to measure fifteen different aromatic stacking interactions as a function of substituent (NMe2, OMe, Me, Cl and NO2 ). When both aromatic rings have electron-withdrawing nitro substituents, the interaction is attractive (−2.8 kJ mol −1 ) due to reduced π-electron repulsion. When both aromatic rings have electron-donating di-methylamino substituents, the interaction is repulsive (+2.0 kJ mol −1 ) due to increased π-electron repulsion. The results show that aromatic stacking interactions are dominated by short range electrostatic contacts rather than substituent dipole interactions.